pH-dependent and cathepsin B activable CaCO3 nanoprobe for targeted in vivo tumor imaging - Sun N (Dove Medical Press, 2019)
Ning Sun,1,2,* Dou Wang,3,* Guoqiang Yao,4 Xiaomei Li,1 Ting Mei,1 Xinke Zhou,1 Kwok-Yin Wong,2 Baishan Jiang,4 Zhiyuan Fang,11The Fifth Affiliated Hospital of Guangzhou Medical University, Guangzhou 510500, People’s Republic of China; 2State Key Laboratory of Chemical Biology and Drug Discovery, and Department of Applied Biology and Chemical Technology, The Hong Kong Polytechnic University, Hung Hom, Kowloon, Hong Kong SAR, People’s Republic of China; 3Department of Hepatobiliary and Pancreatic Surgery, Shenzhen People‘s Hospital, Second Clinical Medical College of Jinan University, Shenzhen 518020, People’s Republic of China; 4Guangzhou Institutes of Biomedicine and Health, Chinese Academy of Sciences, Guangzhou 510530, People’s Republic of China*These authors contributed equally to this work Background: The intraoperative visualization of tumor cells is a powerful modality for surgical treatment of solid tumors. Since the completeness of tumor excision is closely correlated with the survival of patients, probes that can assist in distinguishing tumor cells are highly demanded.Purpose: In the present study, a fluorescent probe JF1 was synthesized for imaging of tumor cells by conjugating a substrate of cathepsin B (quenching moiety) to Oregon Green derivative JF2 using a self-immolative linker.Methods: JF1 was then loaded into the folate-PEG modified CaCO3 nanoparticles. The folate receptor-targeted, pH-dependent, and cathepsin B activable CaCO3 nanoprobe was test in vitro and in vivo for tumor imaging.Results: CaCO3 nanoprobe demonstrated good stability and fast lighting ability in tumors under low pH conditions. It also showed lower fluorescence background than the single cathepsin B dependent fluorescent probe. The pH-dependent and cathepsin B controlled “turn-on” property enables precise and fast indication of tumor in vitro and in vivo.Conclusion: This strategy of controlled drug delivery enables in vivo imaging of tumor nodules with a high signal-to-noise ratio, which has great potential in surgical tumor treatment.Keywords: cathepsin B, activable probe, fluorescent probe, CaCO3 nanoparticle, tumor imaging